The Relevance of the Application of the Presidential Threshold and the Implementation of Simultaneous Elections in Indonesia - Rizki Bagus Prasetio; Febri Sianipar (Law and Human Rights Policy Strategy Agency, Ministry of Law and Human Rights of The Repub, 2021)
This research is intended to discuss the relevance of the application of presidential threshold and the implementation of simultaneous general elections in Indonesia. The concept of simultaneous general elections is the implementation of legislative and executive elections which are carried out simultaneously. The implementation of the first simultaneous general elections in Indonesia was motivated by a request for a judicial review of Law Number 42 Year 2008 concerning the Election of the President and Vice President. The Constitutional Court issued the Constitutional Court Decision Number 14/PUU-IX/2013 with the decision granting part of the request which later gave birth to the implementation of simultaneous elections in Indonesia starting in 2019. However, from the various articles that were reviewed, there was one article that was not decided by the Constitutional Court, namely regarding the presidential threshold. The Constitutional Court is of the opinion that the regulation regarding the presidential threshold is an open legal policy for the legislature. This paper is a normative legal research, with conceptual approach and statute approach to find answers to existing problems. The research source used is secondary data consisting of primary legal materials and secondary legal materials as explanation for primary legal materials. From the results of this research, it was found that the simultaneous elections and the presidential threshold were not compatible. On the one hand, the presidential threshold aims to simplify the number of parties.